Risk factors of computer vision syndrome in students during online learning period - Reva Maya Tika; Laila Fitria (Intelektual Pustaka Media Utama, 2023)
The COVID-19 pandemic poses a risk of increasing cases of computer vision syndrome (CVS) due to changes in the environment for work and study because of the implementation of the Work/Study from Home policy. This study aimed to determine the risk factors associated with CVS in students. The study design was cross-sectional with the population of bachelor program students, with a sample size of 124 students. Data were collected through online questionnaires. Data analysis was carried out to study the statistical relationship between the independent variables and the dependent variable using the Chi-Square test. This study showed that the prevalence of CVS among students was 87.1%. The analysis showed that one variable had a significant relationship with CVS in students, namely emotional exhaustion (OR 5.47, 95% CI: 1.75-17.02). Another variable, although not significant, was considered to play a role as a risk factor for CVS, namely the duration of computer use (OR 4.75, 95% CI: 1.02-22.25). Emotional exhaustion and duration of computer use are important risk factors in the occurrence of CVS in students during the online learning period. It is necessary to increase socialization regarding the ergonomics of using computers and stress management to prevent CVS in students.